Application of GNU Octave in Simulating Dynamic Electrical Physics Concepts on BLDC Electric Motor Trainer Kits - Alfat Khaharsyah; Aditya Yoga Purnama; Rabiman; Alfath Maulana Apriadna (Postgraduate, University of Mataram, 2025)
The study of dynamic electrical physics among first-semester students is often unpopular because it is considered abstract and difficult to relate to real-world applications. To foster a positive attitude and interest in the subject matter, contextual and technology-based learning strategies are needed. This study aims to apply a simulation of a BLDC electric motor using the open-source software GNU Octave in the context of electric vehicles, as well as to describe students' affective responses after participating in the learning activity. The study employs a quantitative descriptive approach with participants being students from the Physics Education and Vocational Mechanical Engineering Education programs. The simulation was developed based on the mathematical model of the BLDC electric motor and visualized using numerical methods in GNU Octave. After participating in the simulation-based learning activity, students were asked to complete a questionnaire measuring affective aspects such as interest, motivation, and attitude toward physics learning based on applications. The questionnaire results indicated that the majority of students responded positively to the use of simulations. The research results indicate that over 90% of students demonstrated interest, motivation, and positive attitudes toward simulation-based physics learning on electric motors. Students also evaluated GNU Octave as an attractive, free, and relevant tool for learning needs in the digital age. Thus, the application of GNU Octave as a simulation medium not only supports conceptual understanding indirectly but is also effective in fostering students' affective aspects toward physics and electric vehicle technology learning.